2007
DOI: 10.2353/ajpath.2007.061083
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Interleukin-1 Signaling Cascades in Normal and Osteoarthritic Articular Cartilage

Abstract: Interleukin (IL)-1 is one of the most important catabolic cytokines in rheumatoid arthritis. In this study, we were interested in whether we could identify IL-1 expression and activity within normal and osteoarthritic cartilage. mRNA expression of IL-1␤ and of one of its major target genes, IL-6, was observed at very low levels in normal cartilage, whereas only a minor up-regulation of these cytokines was noted in osteoarthritic cartilage, suggesting that IL-1 signaling is not a major event in osteoarthritis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
96
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 42 publications
6
96
0
1
Order By: Relevance
“…Whereas inhibition of Rho/ROCK activation by TGFa prevents changes in chondrocyte shape, MEK/ERK signaling inhibition rescues the suppression of ECM gene expression and SOX9. Our results align with previous studies that have described roles for MEK/ERK signaling in articular cartilage degeneration 19,20,48 and point to a similar role for Rho/ROCK. This report also adds to the growing body of evidence indicating that inappropriate activation of the EGFR leads to cartilage degradation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Whereas inhibition of Rho/ROCK activation by TGFa prevents changes in chondrocyte shape, MEK/ERK signaling inhibition rescues the suppression of ECM gene expression and SOX9. Our results align with previous studies that have described roles for MEK/ERK signaling in articular cartilage degeneration 19,20,48 and point to a similar role for Rho/ROCK. This report also adds to the growing body of evidence indicating that inappropriate activation of the EGFR leads to cartilage degradation.…”
Section: Discussionsupporting
confidence: 82%
“…18 Furthermore, MEK/ERK and p38 MAPK (mitogen-activated protein kinase) signaling are implicated in the degenerative processes in articular cartilage. 19,20 Therefore, we hypothesized that these pathways also mediate TGFa signaling in articular chondrocytes and the induction of cartilage degradation. The results of our study show that TGFa activates several intracellular pathways including RhoA/ROCK and MEK/ERK and that each pathway mediates specific aspects of the cartilage response to TGFa.…”
mentioning
confidence: 99%
“…Before drawing conclusions regarding the role of these proteases in the development of posttraumatic OA, these patients will need to be followed over time to evaluate if these MMPs and aggrecan degradation are more strongly correlated with the ultimate development of posttraumatic OA. Prior studies have suggested various cell-signaling mechanisms that may play a role in the development of posttraumatic OA including transforming growth factor-b, endothelin-1, interleukin-1b, and NF-jB [12,15,22,33,37,38]. Our current study should draw attention to the postinjury presence of MMPs and aggrecan degradation as potentially playing a role in progression to OA as well.…”
Section: Discussionmentioning
confidence: 99%
“…Increased IL-1β and TNF-α levels are considered important influence factors in OA and RA and many therapeutic target (Cawston et al, 2003;Fan et al, 2007). Previous studies have shown that IL-1β and TNF-α can up-regulate aggrecanase expressions in OA and RA (Fan et al, 2007;Arner et al, 1998), which would predominantly increase aggrecan degradation and lead to glycosaminoglycan loss from the cartilage. Similar to OA and RA, it has been confirmed that IL-1β and TNF-α levels are also increased in adult KBD patients' synovial fluid (Tong and Yang, 2000).…”
Section: Discussionmentioning
confidence: 99%